Assuring the long-term total joint arthroplasty: a triad of variables. (January 2019) - Kayani, B.; Konan, S.; Thakrar, R. R.; Huq, S. S.; Haddad, F. S.
Abstract : Objectives: The primary objective of this study was to compare accuracy in restoring the native centre of hip rotation in patients undergoing conventional manual total hip arthroplasty (THA) versus robotic-arm assisted THA. Secondary objectives were to determine differences between these treatment techniques for THA in achieving the planned combined offset, component inclination, component version, and leg-length correction. Materials and Methods: This prospective cohort study included 50 patients undergoing conventional manual THA and 25 patients receiving robotic-arm assisted THA. Patients undergoing conventional manual THA and robotic-arm assisted THA were well matched for age (mean age, 69.4 years (sd 5.2) vs 67.5 years (sd 5.8) (p = 0.25); body mass index (27.4 kg/m 2 (sd 2.1) vs 26.9 kg/m 2 (sd 2.2); p = 0.39); and laterality of surgery (right = 28, left = 22 vs right = 12, left = 13; p = 0.78). All operative procedures were undertaken by a single surgeon using the posterior approach. Two independent blinded observers recorded all radiological outcomes of interest using plain radiographs. Results: The correlation coefficient was 0.92 (95% confidence interval (CI) 0.88 to 0.95) for intraobserver agreement and 0.88 (95% CI 0.82 to 0.94) for interobserver agreement in all study outcomes. Robotic THA was associated with improved accuracy in restoring the native horizontal (p < 0.001) and vertical (p < 0.001) centres of rotation, and improved preservation of the patient's native combined offset (p < 0.001) compared with conventional THA. Robotic THA improved accuracy in positioning of the acetabular component within the combined safe zones of inclination and anteversion described by Lewinnek et al (p = 0.02) and Callanan et al (p = 0.01) compared with conventional THA. There was no difference between the two treatment groups in achieving the planned leg-length correction (p = 0.10). Conclusion: Robotic-arm assisted THA was associated with improved accuracy in restoring the native centre of rotation, better preservation of the combined offset, and more precise acetabular component positioning within the safe zones of inclination and anteversion compared with conventional manual THA.